2021
DOI: 10.3390/diagnostics11122170
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Markers of Survival among Japanese Patients with Anaplastic Lymphoma Kinase-Positive Non-Small-Cell Lung Cancer Receiving First-Line Alectinib

Abstract: The prognoses of patients with non-small-cell lung cancer (NSCLC) harboring anaplastic lymphoma kinase (ALK) gene rearrangement have dramatically improved with the use of ALK tyrosine kinase inhibitors. Although immunological and nutritional markers have been investigated to predict outcomes in patients with several cancers, their usefulness in targeted therapies is scarce, and their significance has never been reported in patients receiving first-line treatment with alectinib. Meanwhile, neutrophil-to-lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A study of the Chinese Academy of Medical Sciences confirmed that in ALK -positive NSCLC patients treated with crizotinib, the trend of NLR, derived NLR [dNLR = neutrophil count/(white blood cell count-neutrophil count)], PLR, and HGB can be used to assess a patient’s progress ( 15 ). A Japanese study noted that immunological and nutritional markers could be useful in predicting the outcomes of first-line treatment with alectinib ( 32 ). In our study, NLR was not only an independent prognostic factor in univariate and multivariate analysis, but also changes in NLR before and after treatment can reflect the efficacy and be used to further predict survival.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the Chinese Academy of Medical Sciences confirmed that in ALK -positive NSCLC patients treated with crizotinib, the trend of NLR, derived NLR [dNLR = neutrophil count/(white blood cell count-neutrophil count)], PLR, and HGB can be used to assess a patient’s progress ( 15 ). A Japanese study noted that immunological and nutritional markers could be useful in predicting the outcomes of first-line treatment with alectinib ( 32 ). In our study, NLR was not only an independent prognostic factor in univariate and multivariate analysis, but also changes in NLR before and after treatment can reflect the efficacy and be used to further predict survival.…”
Section: Discussionmentioning
confidence: 99%
“…16 studies with 2378 patients(16-18, 21,22,27,30,32,34,36,37,39,41,42,44,47) showed an association between the SII and PFS in NSCLC. Heterogeneity was signi cant (I 2 = 83.1%, P < 0.001), and a random-effects model was performed.…”
Section: Sii and Pfs In Nsclcmentioning
confidence: 99%
“…Subsequently, 13 studies were eliminated because 9 studies did not provide survival data, full-text articles of 2 studies were not available, and 2 studies were comments. Finally, a total of 32 studies involving 12,040 patients were included 47). (Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ALK mutation in patients with non-small cell lung cancer who received appropriate first-line targeted therapy, the duration of PFS was determined to be associated with baseline PLR, and SII, as well as the SII, score three weeks after initiation of therapy. Indexes were measured before and three weeks after drug administration [18]. Ju et al found that lower SII was associated with prolonged survival in patients with different EGFR mutant lung adenocarcinomas.…”
Section: Figure 1 -Roc Curve Analysis For Optimal Cut-off Value Of In...mentioning
confidence: 99%